The Role Of Risk, Trust, Social Influence On ZIS Online Payment Adoption: Generation-Z Perspectives - Tri Wahyu Oktavendi; Immanuel Mua'ammal (Jurnal Reviu Akuntansi dan Keuangan, 2021)
Technological developments encourage people to make changes in their lives. The emergence of various kinds of online payment systems has made human life easier in completing various transaction activities. With online payment technology, ZIS payment activities can be done cashless. The respondents in this study were Generation Z. This research’s testing is using SMART PLS 3.0. Generation Z has several factors that are considered to be intense in using ZIS online Payment. To be able to continue to be intense, one of them is by increasing trust in ZIS online Payment. Trust owned by Generation Z is driven by the factors of Risk, Ease of Use, Usefulness, and Social Influence. The implication of the results of this study is that by increasing the ZIS online Payment movement in the future, ZIS transactions will be faster and the ability of the Amil Zakat, Infaq, and Shadaqah bodies to collect ZIS funds will also increase.